Optimasi Web Profil dan Sistem Informasi Terintegrasi Sebagai Media Promosi Wisata Waduk Pondok Ngawi - Nanda dwi pamungkas; Ridho Pamungkas; Saifulloh (LPPM Universitas Merdeka Madiun, 2021)
This research was conducted with the aim of designing and creating a web profile and integrated tourism information system that can present and provide tourist information in the Pondok Reservoir, Ngawi Regency. The background of this research was appointed based on the need for an information system that can provide comprehensive information quickly and accurately. There is still a lack of information that can be consumed by the wider community in relation to information on tourist attractions, especially Pondok Reservoir, so it is necessary to create an effective alternative means in informing the Pondok Reservoir tourism so that it is increasingly known by the wider community. And with this web profile and information system, it can also help the local government of the Department of Tourism and Culture in managing tourism and cultural information in the Ngawi Regency area. This study uses the waterfall system development method and the system testing method using the Black box testing method which focuses on the website function keys.